(untitled) (Signo & Seña, 2016)
This article is based on a sociolinguistic ethnography in a multicultural and multilingual primary school in downtown Barcelona. The focus of the research are interactions between volunteers and learners in an after-school reading program run by a non-profit organisation for 4th and 5th grade students. Considering that plurilingual and pluriliteracy skills are necessary in globalised contexts, it is paradoxical that students who are ‘pre-equipped’ with diverse repertoires – but ones that are socially and educationally less valued – are also those most vulnerable. Different contexts, approaches and practices conducive to education inclusive of students’ repertoires are in need of description. So too is research contributing to empowering learning experiences. The systematic observation of interactions between children and volunteers allows certain transgressive spaces and practices to be identified, which challenge the status quo. It is precisely in such spaces and practices that we believe potential for transforming educational praxis and trajectories lies.